1998
DOI: 10.1042/bj3350329
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell polyamine homeostasis is altered by the radioprotector WR1065

Abstract: Mammalian cells become more susceptible to radiation-induced death and mutagenesis when restricted in their production of the natural polyamines putrescine, spermidine and spermine. The effects of polyamine deprivation are reversed by N-(2-mercaptoethyl)-1, 3-diaminopropane (WR1065), a simple aminothiol that has been extensively studied for its radioprotectant properties. Because this compound and its oxidized derivative WR33278 bear some resemblance to the polyamines, it was hypothesized that radioprotection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…WR1065 and its oxidized dissulĀ®te linked WR33278 show chemical structures similar to those of naturally occurring polyamines such as spermidine (Wyatt et al, 1989;Mitchell et al, 1998). To determine whether spermidine may also activate p53, we treated MCF-7 cells with increasing concentrations of either WR1065 or spermidine.…”
Section: Spermidine Does Not Induce P53mentioning
confidence: 99%
“…WR1065 and its oxidized dissulĀ®te linked WR33278 show chemical structures similar to those of naturally occurring polyamines such as spermidine (Wyatt et al, 1989;Mitchell et al, 1998). To determine whether spermidine may also activate p53, we treated MCF-7 cells with increasing concentrations of either WR1065 or spermidine.…”
Section: Spermidine Does Not Induce P53mentioning
confidence: 99%
“…Aminothiols protect against ionizing radiation by scavenging hydroxyl radicals, transferring hydrogen to DNA radicals, and causing hypoxia near DNA [Purdie et al, 1983;Schwartz et al, 1988;Smoluk et al, 1988a;Hospers et al, 1999]. Other mechanisms that may contribute to radioprotection by WR-1065 are its causing increased synthesis of radioprotective polyamines [Mitchell et al, 1998], protecting sulfhydryl enzymes [Hospers et al, 1999], affecting enzymes of DNA synthesis [Grdina et al, 1994], and facilitating DNA repair [Grdina et al, 1999;Hospers et al, 1999]. Radioprotective effects of the polyamines spermine [Chiu and Oleinick, 1997] and spermidine [Newton et al, 1997] can be ascribed to scavenging of hydroxyl radicals and the compaction or stabilization of chromatin.…”
Section: Discussionmentioning
confidence: 95%
“…Ames and Dubin [1960] reported that polyamines inhibited replication of T4 bacteriophage. Mitchell et al [1998] showed that WR1065 increased intracellular spermidine levels in cells exposed in vitro. Such a change has been suggested to have antimutagenic effects because of the DNA protective capacity of spermidine, and also could result in antiviral effects because of changes in intracellular polyamine levels [Bachrach and Rosenkovitch, 1972;Bachrach, 2007].…”
Section: Discussionmentioning
confidence: 99%